2020
DOI: 10.1044/2019_ajslp-cac48-18-0227
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Fidelity Procedures for an Aphasia Intervention Within a Randomized Controlled Trial: Design, Feasibility, and Results

Abstract: Purpose This study reports on the treatment fidelity procedures implemented during a 5-year randomized controlled trial comparing intensive and distributed comprehensive aphasia therapy. Specifically, the results of 1 treatment, verb network strengthening treatment (VNeST), are examined. Method Eight participants were recruited for each of 7 consecutive cohorts for a total of 56 participants. Participants completed 60 hr of aphasia therapy, including 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…The study was novel as one of still only a handful of aphasia trials reporting fidelity in a systematic way, based on a theoretical framework. 33 39 42 43 The study demonstrated the importance of comprehensive planning for fidelity at the outset of a trial and the need for ongoing rigorous monitoring throughout the trial to ensure an intervention is implemented as intended. Twitter Nicholas Behn @NicholasBehn, Becky Moss @BeckMoss, Sally McVicker @sallymcvicker, Abi Roper @abracabadger, Sarah Northcott @sarahnorthcott8, Shirley Thomas @DrShirleyThomas, Alan Simpson @cityalan, Kimberley Goldsmith @KimberleyGol and Katerina Hilari @KaterinaHilari…”
Section: Discussionmentioning
confidence: 99%
“…The study was novel as one of still only a handful of aphasia trials reporting fidelity in a systematic way, based on a theoretical framework. 33 39 42 43 The study demonstrated the importance of comprehensive planning for fidelity at the outset of a trial and the need for ongoing rigorous monitoring throughout the trial to ensure an intervention is implemented as intended. Twitter Nicholas Behn @NicholasBehn, Becky Moss @BeckMoss, Sally McVicker @sallymcvicker, Abi Roper @abracabadger, Sarah Northcott @sarahnorthcott8, Shirley Thomas @DrShirleyThomas, Alan Simpson @cityalan, Kimberley Goldsmith @KimberleyGol and Katerina Hilari @KaterinaHilari…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 papers generated, 6 were aphasia intervention studies which reported also on the TF of the study as part of the paper(Cherney et al 2019, Hilari et al 2019, Marshall et al 2018, Shrubsole et al 2018, Volkmer et al 2018. 5 were looking solely at the TF reporting of a specific aphasia intervention, as this paper intends to do(Ball et al 2018, Carragher et al 2019, Conlon et al 2020, Kladouchou et al 2017, Spell et al 2020). It should be noted that 3 were study protocol papers, and were therefore giving only intended TF reporting processes(Carragher et al 2019, Hilari et al 2019, Volkmer et al 2018.…”
mentioning
confidence: 99%
“…More subtle aspects of dose, such as levels of practice on target items, were neglected. 7 papers explicitly addressed use of a manual to improve TF(Carragher et al 2019, Conlon et al 2020, Hilari et al 2019, Kladouchou et al 2017, Marshall et al 2020, Spell et al 2020, Volkmer et al 2018. 9 reported use, or intended use, of videos to record the intervention and assess TF(Ball et al 2018, Carragher et al 2019, Conlon et al 2020, Hilari et al 2019, Kladouchou et al 2017, Marshall et al 2018, Spell et al 2020, Volkmer et al 2018.…”
mentioning
confidence: 99%
See 2 more Smart Citations